Answer:
true
Step-by-step explanation:
Answer:The pictures not that clear
Step-by-step explanation:
Answer is <span>C) 7√(5)
cause
</span><span>√(5) + 6√(5)
</span>=<span>√5 (1+6)
</span>= 7<span>√5</span>
Answer:
—6
Explanation:
In an expression with a negative number and a positive number, the negative will come on top. This meaning the product (end piece) will be negative. In this problem despite the signs we know 3•2 is 6. Now since one number is negative (3) and the other is positive (2) negative will come out on top.
* KEEP IN MIND *
+ and + = positive
- and + = negative
Easy Memo for Multiplication and Divison:
“Same sign add, different sign subtract”
Add = Positive (+)
Subtract = Negative (-)